Assessing brain function in stressed healthy individuals following the use of a combination of green tea, Rhodiola, magnesium, and B vitamins: an fMRI study - Pickering, Gisèle; Noah, Lionel; Pereira, Bruno; Goubayon, Jonathan; Leray, Vincent; Touron, Ambre; Macian, Nicolas; Bernard, Lise; Dualé, Christian; Roux, Veronique; Chassain, Carine (Frontiers in Nutrition, 2023)
Introduction This randomized, controlled, single-blinded trial assessed the effect of magnesium (Mg)-Teadiola (Mg, vitamins B6, B9, B12, Rhodiola, and green tea/L-theanine) versus placebo on the brain response to stressful thermal stimulus in chronically stressed, but otherwise healthy subjects. Impacts on stress-related quality-of-life parameters (depression, anxiety, sleep, and perception of pain) were also explored. Methods The study recruited a total of 40 adults (20 per group), suffering from stress for more than 1 month and scaling ≥14 points on the Depression Anxiety Stress Scale (DASS)-42 questionnaire at the time of inclusion. Individuals received oral Mg-Teadiola or placebo for 28 days (D). fMRI analysis was used to visualize the interplay between stress and pain cerebral matrices, using thermal stress model, at baseline (D0) and after D28. Results Based on blood-oxygen-level-dependent (BOLD) signal variations during the stress stimulation (before pain perception), a significantly increased activation between D0 and D28 was observed for left and right frontal area (p = 0.001 and p = 0.002, respectively), left and right anterior cingulate cortex (ACC) (p = 0.035 and p = 0.04, respectively), and left and right insula (p = 0.034 and p = 0.0402, respectively) in Mg-Teadiola versus placebo group. During thermal pain stimulation, a significantly diminished activation of the pain matrix was observed between D0 and D28, for left and right prefrontal area (both p = 0.001), left and right insula (p = 0.008 and p = 0.019, respectively), and left and right ventral striatum (both p = 0.001) was observed in Mg-Teadiola versus placebo group. These results reinforce the clinical observations, showing a perceived benefit of Mg-Teadiola on several parameters. After 1 month of treatment, DASS-42 stress score significantly decreased in Mg-Teadiola group [effect size (ES) −0.46 (−0.91; −0.01), p = 0.048]. Similar reductions were observed on D14 (p = 0.011) and D56 (p = 0.008). Sensitivity to cold also improved from D0 to D28 for Mg-Teadiola versus placebo [ES 0.47 (0.02; 0.92) p = 0.042]. Conclusion Supplementation with Mg-Teadiola reduced stress on D28 in chronically stressed but otherwise healthy individuals and modulated the stress and pain cerebral matrices during stressful thermal stimulus.